Tourette disorder and sleep - Justin L. Blaty; Lourdes M. DelRosso (Biomedical Journal, 2022)
Healthy sleep is of utmost importance for growth, development, and overall health. Strong evidence shows that sleep is affected negatively in patients and particularly children with Tourette Disorder (TD). There is also a frequent association of TD with Attention Deficit Hyperactivity Disorder (ADHD) which alone has negative effects on sleep and cumulatively worsens the associated sleep findings. The most consistent polysomnographic findings in patients with TD is decreased total sleep time, lower sleep efficiency and an elevated arousal index. Polysomnography studies have confirmed the presence of movements and persistence of tics during both Rapid Eye Movement (REM) and NREM sleep [1]. In general Patients with TD are found to have an increased incidence of sleep onset and sleep maintenance insomnia. Some studies have shown increased incidence of parasomnias (including sleepwalking, sleep talking and night terrors), but this may be confounded by the increased underlying sleep disruptions seen in TD. The hypersomnolence found in patients with TD is also suggested to be secondary to the underlying TD sleep disruption. There is not a significant association with sleep disordered breathing or circadian rhythm disorders and TD. Treatment of underlying TD is important for the improvement of sleep related TD manifestations and is outlined in this review.